Organic synthesis using biocatalysis - Goswami, Animesh; Stewart, Jon D. (Amsterdam : Elsevier, 2016)
Organic Synthesis Using Biocatalysis provides a concise background on the application of biocatalysis for the synthesis of organic compounds, including the important biocatalytic reactions and application of biocatalysis for the synthesis of organic compounds in pharmaceutical and non-pharmaceutical areas. The book provides recipes for carrying out various biocatalytic reactions, helping both newcomers and non-experts use these methodologies. It is written by experts in their fields, and provides both a current status and future prospects of biocatalysis in the synthesis of organic molecules.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed September 11, 2015)
Elsevier
Keywords: Organic compounds -- Synthesis; Biocatalysis; SCIENCE / Chemistry / Organic; Biocatalysis; Organic compounds -- Synthesis; Electronic books